Climate service value chain towards end users - Nguyen, Duy Nhiem; Dam, Viet Bac; Le Thi Tam; Simelton, Elisabeth; Swaans, Cornelis P.M.; Barlis, Angelica (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
With the purpose of contributing to the development of agro-climatic research and services in Vietnam, within the framework of cooperation between the Vietnam Institute of Meteorology, Hydrology and Climate Change (IMHEN) and CARE International in Vietnam, a technical and national workshop on “Agro-Climate Services: Needs and Opportunities” was organized to review the current status of climate information services in agriculture, as well as the needs, challenges and opportunities to develop climate information services in the sector. CARE, ICRAF and the Alliance of Bioversity International and CIAT have put together a presentation to further introduce the climate service value chain and its stages and how it relates to the needs of the end users of information, primarily, smallholder farmers. Several cases and experiences at different levels were presented during the workshop highlighting the lessons learned from Ha Tinh province and initial findings from the Mekong River Delta.